2021
DOI: 10.3390/vaccines9111356
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Bifidobacterium Strains Enhance the Efficacy of Neo-Epitope Based Cancer Vaccines

Abstract: A large body of data both in animals and humans demonstrates that the gut microbiome plays a fundamental role in cancer immunity and in determining the efficacy of cancer immunotherapy. In this work, we have investigated whether and to what extent the gut microbiome can influence the antitumor activity of neo-epitope-based cancer vaccines in a BALB/c-CT26 cancer mouse model. Similarly to that observed in the C57BL/6-B16 model, Bifidobacterium administration per se has a beneficial effect on CT26 tumor inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
(92 reference statements)
1
13
0
Order By: Relevance
“…Growing evidence revealed that Muribaculaceae was enriched by tumor challenge and increased in obese and type 2 diabetes mellitus rats, which was correlated with glucose and lipid metabolisms and immunoreaction. [ 49–51 ] Moreover, it was positively related with proinflammatory metabolites and systemic inflammation, [ 52 ] which is basically consistent with the results of this study. However, previous studies have been suggested that Muribaculaceae as probiotics is involved in gut microbial remodeling and disease alleviation, [ 53 ] indicating that the role of Muribaculaceae is extremely intricate and should be separately discussed in specific situations.…”
Section: Discussionsupporting
confidence: 90%
“…Growing evidence revealed that Muribaculaceae was enriched by tumor challenge and increased in obese and type 2 diabetes mellitus rats, which was correlated with glucose and lipid metabolisms and immunoreaction. [ 49–51 ] Moreover, it was positively related with proinflammatory metabolites and systemic inflammation, [ 52 ] which is basically consistent with the results of this study. However, previous studies have been suggested that Muribaculaceae as probiotics is involved in gut microbial remodeling and disease alleviation, [ 53 ] indicating that the role of Muribaculaceae is extremely intricate and should be separately discussed in specific situations.…”
Section: Discussionsupporting
confidence: 90%
“…Another method is that the microbiota can enhance vaccine response via activation of convergent pathways, leading to a greater response than the vaccine would cause alone. • The application of probiotic bifidobacteria has been shown to enhance the immune response to a neoepitope-based cancer vaccine 293 . This was suggested to be caused by the probiotic leading to an increase in taxa with high sequence similarity to the neoepitope, leading to further immune stimulation.…”
Section: Methods Of Microbiome-based Interventions Their Rationales A...mentioning
confidence: 99%
“…• The application of probiotic bifidobacteria has been shown to enhance the immune response to a neoepitope-based cancer vaccine 293 . This was suggested to be caused by the probiotic leading to an increase in taxa with high sequence similarity to the neoepitope, leading to further immune stimulation.…”
Section: Methods Of Microbiome-based Interventions Their Rationales A...mentioning
confidence: 99%
“…There is growing evidence that the variety and composition of gut bacteria influence the therapeutic efficacy of various cancer treatments [19,[34][35][36][37][38][39][40][41]. In 1910, Coley WB, for the first time, injected streptococcal organisms into a patient suffering from unresectable sarcoma, resulting in excellent antitumor responses [42].…”
Section: The Impact Of Microbiome On Cancer and Cancer Therapeuticsmentioning
confidence: 99%